2015
DOI: 10.4103/2229-3485.167094
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of oral gabapentin versus clonidine as premedication on preoperative sedation and laryngoscopic stress response attenuation for the patients undergoing general anesthesia

Abstract: Background:Laryngoscopy and endotracheal intubation (L and I) is associated with rise in blood pressure (BP), heart rate (HR), leading to adverse cardiological outcome especially in susceptible individuals. To compare the BP, HR during L and I as well as to evaluate the preoperative sedation status between oral clonidine (Group C) and oral gabapentine (Group G) as premedication for the patients undergoing major surgery under general anesthesia (GA).Materials and Methods:From April 2008 to December 2009; in a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
(26 reference statements)
0
2
1
Order By: Relevance
“…Also, our results are in concordance with Singhal et al [ 5 ] who compared oral clonidine 200 mcg and gabapentin 900 mg administered 90 minutes before induction, which showed blood pressure below baseline in the clonidine group in comparison with the gabapentin group. However, our results are slightly different from those of the study conducted by Majumdar et al [ 4 ] in which oral clonidine (200 mcg) and oral gabapentin (600 mg) were administered before surgery, and clonidine was found to be better at attenuating hemodynamic parameters before induction, during laryngoscopy, and orotracheal intubation at zero, first, third, and fifth minutes while gabapentin attenuated HR and MAP at seventh and 10th minutes. This may be due to the high dose of gabapentin administered in this trial compared to our study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Also, our results are in concordance with Singhal et al [ 5 ] who compared oral clonidine 200 mcg and gabapentin 900 mg administered 90 minutes before induction, which showed blood pressure below baseline in the clonidine group in comparison with the gabapentin group. However, our results are slightly different from those of the study conducted by Majumdar et al [ 4 ] in which oral clonidine (200 mcg) and oral gabapentin (600 mg) were administered before surgery, and clonidine was found to be better at attenuating hemodynamic parameters before induction, during laryngoscopy, and orotracheal intubation at zero, first, third, and fifth minutes while gabapentin attenuated HR and MAP at seventh and 10th minutes. This may be due to the high dose of gabapentin administered in this trial compared to our study.…”
Section: Discussioncontrasting
confidence: 99%
“…Pneumoperitoneum created during laparoscopy results in hypercapnia, which in turn causes adverse cardiac effects such as tachycardia, hypertension, an increase in systemic vascular resistance, and a decrease in cardiac output [ 3 ]. The adverse cardiac effects due to pneumoperitoneum can be aggravated by the pressor response to laryngoscopy and endotracheal intubation [ 4 , 5 ]. Many pharmacological agents like clonidine and gabapentin have been evaluated as oral premedications; moreover, intravenous drugs such as vasodilators (nitroglycerine), opioids (fentanyl), beta-blockers (esmolol), and calcium channel blockers can be administered prior to abdominal insufflation to attenuate the hemodynamic response to pneumoperitoneum [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fulas et al [ 27 ] described a topical combination of clonidine and pentoxifylline that significantly affects neuropathic pain. A research article by Majumdar et al [ 40 ] revealed that gabapentin and clonidine have similar soothing effects before surgeries. Hence clonidine is more effective on laryngoscopy compared to gabapentin.…”
Section: Discussionmentioning
confidence: 99%